erw - Maulana Riski; Dikdik Fauzi Dermawan; Akhmad Dimyati (Universitas Hamzanwadi, 2026)
Mastery of basic motor skills such as throwing, catching, and hitting in baseball is often low among students, presumably due to the use of teaching methods that do not actively engage students. This study aims to examine the effect of the problem-based learning (PBL) model on improving these basic motor skills. The research method used a quantitative approach with a one-group pretest-posttest design. A total of 30 ninth-grade students at Tunas Dharma Junior High School were selected as samples using purposive sampling. The research instrument was a motor skills test that had been tested for validity and reliability. The data were analyzed using prerequisite tests (normality and homogeneity) and hypothesis testing using the Paired Sample t-Test. The results showed a significant increase in all three aspects of skill. The average score increased from 66.63 to 74.50 for throwing, 71.47 to 77.57 for catching, and 71.47 to 77.07 for hitting. The statistical test results reinforced these findings with a significance value of 0.000 (< 0.05) for all variables. The research conclusion proves that the PBL model has a positive and significant effect on improving students' motor skills in baseball learning, making it a viable alternative learning strategy in physical education.